TRAC 2010 : proceedings of the twentieth annual Theoretical Roman Archaeology Conference which took place at the University of Oxford, 25-28 March, 2010 - Mladenović, Dragana, 1977 November 12-; Russell, Ben, 1984- (Oxbow Books, 2011)
Many papers were given during the annual conference, covering the breadth and length of the Roman world. This volume contains a selection of the papers from all of the sessions.